A Systematic Review of the Intelligent Digital Storytelling Process in Disseminating Health Information - Eambunnapong, Kawitsara; Nilsook, Prachyanun; Wannapiroon, Panita (International Journal of Online and Biomedical Engineering (iJOE), 2023)
Digital storytelling is a new concept in education that involves creating meaning. It is a tool with great potential, but in Thailand, it is currently not very popular in terms of sharing stories about disease. This review analyzes the components and processes of intelligent digital storytelling to aid the development of an intelligent digital storytelling platform for disseminating health information. Based on the synthesis of relevant documents, the research process involves 9 main steps: 1) identifying the review objectives, 2) reviewing research questions, 3) determining inclusion criteria, 4) finding relevant studies, 5) selecting documents, 6) data extraction, 7) arriving at a conclusion, 8) document synthesis and 9) discussion of the results. A study of articles from the PRISMA Checklist published between 2017 and 2022 revealed that ultimately only 47 articles met the inclusion criteria. From the analysis of the data, it was found that there are four main elements and 16 sub-components of intelligent digital storytelling. There are 12 steps in the process of intelligent digital storytelling with regard to health information dissemination. The optimal length of an intelligent digital narrative video clip relating to health information dissemination is approximately 2-5 minutes when it comes to achieving the best knowledge of health information.